Determining Bouncepoints in the South of Kalimantan Island for SS Wave Phase - Fahruddin Fahruddin; Gusti Aldy; Muhammad Rasyid Ridho; Ibrahim Ibrahim; Nurlina Nurlina; Sudarningsih Sudarningsih; Mustaid Yusuf; Syamsurijal Rasimeng; La Ode Safiuddin (Lambung Mangkurat University Press, 2023)
The bouncepoints or reflection point of a seismic wave is very important to determine a research area that utilizes SS precursors data. In this study the data used has criteria, to obtain good data. Hence, the research results are also good, while the criteria are: the depth of the earthquake source is limited to less than 75 Km to reduce interference with precursor waves that arrive earlier (sSdiff) and it is easier to determine the bouncepoint. The earthquake source is more than 5.8 Mw to get a good SS phase signal-to-noise ratio (SNR). The best distance between the source and the receiving station is ≥ 1000 to avoid interference with waves reflected on the surface (Ss670s and Ss400s) and ≤ 1650 to avoid interference with ScSScS precursors. The location of this study is in the south of the island of Kalimantan (15 bouncepoints) and there are 3 points data whose bouncepoints is outside the study area. Earthquake data obtained from IRIS (Incorporated Research Institutions for Seismology). The research data for earthquake centers are in Australia, New Zealand and others, for earthquake measuring stations in Europe and Asia.